2015
DOI: 10.1016/j.fertnstert.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age and mental health of offspring

Abstract: The influence of paternal age on the risk for sporadic forms of Mendelian disorders is well known, but a burgeoning recent literature also demonstrates a paternal age effect for complex neuropsychiatric conditions, including schizophrenia, autism, bipolar disorder and even for learning potential, expressed as intelligence. Mental illness is costly to the patients, the family and the public health system, accounting for the largest portion of disability costs in our economy. The delayed onset of neuropsychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 45 publications
(44 reference statements)
0
30
1
1
Order By: Relevance
“…To our best knowledge, parental age has not been evaluated in relation to DUP earlier, although it has been recognized that advanced paternal age at time of birth might bring the age at onset of psychosis forward. 31 The only factor that showed significant effect on DUP in our study was PT openness to experience (B = À0.804, P = 0.024, 95%CI 1.110-4.496). Our finding that patients with psychosis who are more open to experience have shorter treatment delay is a new one and opposite to Compton et al, 12 who found that neuroticism, extraversion, agreeableness and conscientiousness contribute to DUP variation, whilst openness to experience does not.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…To our best knowledge, parental age has not been evaluated in relation to DUP earlier, although it has been recognized that advanced paternal age at time of birth might bring the age at onset of psychosis forward. 31 The only factor that showed significant effect on DUP in our study was PT openness to experience (B = À0.804, P = 0.024, 95%CI 1.110-4.496). Our finding that patients with psychosis who are more open to experience have shorter treatment delay is a new one and opposite to Compton et al, 12 who found that neuroticism, extraversion, agreeableness and conscientiousness contribute to DUP variation, whilst openness to experience does not.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have shown that DUP and indices of premorbid adjustment are not significantly correlated, but the literature related to the abovementioned domain is inconsistent because other authors reported lower premorbid adjustment in patients with longer DUP. To our best knowledge, parental age has not been evaluated in relation to DUP earlier, although it has been recognized that advanced paternal age at time of birth might bring the age at onset of psychosis forward …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study [187], induced DNA damage (nucleotide modifications, single and double strand breaks) in mice sperm via the exposure to ionizing radiation revealed that the number of de novo mutations and clustered mutations were higher in the exposed group when compared to control group. This type of sperm DNA alterations has been associated with autism spectrum syndrome in humans [179, 188]. Similarily, sperm DNA damage was suspected to be involved in behavior or mental alterations in mice [168].…”
Section: Sperm Nuclear/dna Alterations Have Many Facesmentioning
confidence: 93%
“…Jenkins et al [178] found that age-related changes in sperm DNA methylation are located at genes previously associated with schizophrenia, bipolar disorder [178180] and lesser intelligence. In a recent review [179] the evidence of sperm histone and protamine packing involvement on epigenetic inheritance was reaffirmed, the proper compaction of sperm DNA being necessary to avoid access to nucleases and appropriate transcriptional and translational activities. Any alteration in sperm histone retention would affect DNA integrity and could lead to chromatin rearrangements in developmental loci and genes with impacts on embryo development [166, 167].…”
Section: Sperm Nuclear/dna Alterations Have Many Facesmentioning
confidence: 99%
“… 2 The idea that autism’s origins lie in the womb has developed alongside research exploring the effect of environmental factors on sperm and how this, too, may influence offsprings’ risk of autism (Malaspina et al, 2015; Reichenberg et al, 2006). Despite these investigations, to date environmental risks have largely been examined for their effects on the developing fetus in utero , placing attention on women’s bodies as primary conduits for autism risk.…”
mentioning
confidence: 99%